Study on Fault Diagnosis System for Urban Rail Transit Vehicle Bogie Bearing based on Continuous Long and Sloping Route - Fuying Li (Jixie chuandong)
In order to improve the accuracy and effectiveness of the fault diagnosis of the bogie bearing of urban rail transit vehicle， taking the vehicle bogie bearing of Guiyang Metro Line 1 as the research object， the full life cycle fault diagnosis system of the bogie bearing is established by considering the running characteristics of continuous long and sloping route， and the bogie bearing fault diagnosis test platform is established. The research results indicate that the fault diagnosis method of the bogie bearing under the working condition of continuous long and sloping route can accurately extract the impact sample and impact trend curve of the bogie bearing. Under the working condition of continuous long and sloping route， the fault diagnosis system of the bogie bearing has good accuracy and stability， which can monitor the running characteristics of the bogie bearing in real time， and provide important information and technical support for the improvement of maintenance efficiency.